2023
DOI: 10.1200/go.22.00387
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic Features of Breast Cancer in Egypt—Contemporary Profile and Future Needs: A Systematic Review and Meta-Analysis

Abstract: PURPOSE Breast cancer (BC) is the most common cancer among Egyptian females. No current national cancer database is available in Egypt to provide reliable data on the specific clinicopathologic features of BC in this population. Herein, we investigated the clinical profile of BC among Egyptian women. METHODS A systematic review of studies on BC published from inception until December 2021 was performed. We explored pooled estimated proportions of different stages of BC at presentation in Egypt and other clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 46 publications
(181 reference statements)
3
10
0
Order By: Relevance
“…Median age at presentation was 49 with a quarter of patients (5) below 40 years of age and 6 patients between 40–49. The age of presentation in our study is in agreement with studies in Egyptian female cohorts as reported by Azim et al 2023 in their metanalysis. They reported that, the median age of presentation across studies was 50.4 years and about 20% were younger than 40 years (Azim et al 2023 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Median age at presentation was 49 with a quarter of patients (5) below 40 years of age and 6 patients between 40–49. The age of presentation in our study is in agreement with studies in Egyptian female cohorts as reported by Azim et al 2023 in their metanalysis. They reported that, the median age of presentation across studies was 50.4 years and about 20% were younger than 40 years (Azim et al 2023 ).…”
Section: Discussionsupporting
confidence: 93%
“…The age of presentation in our study is in agreement with studies in Egyptian female cohorts as reported by Azim et al 2023 in their metanalysis. They reported that, the median age of presentation across studies was 50.4 years and about 20% were younger than 40 years (Azim et al 2023 ). Screening and early detection for breast cancer remain the best strategies to manage the disease.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In Egypt, more than 22,000 new cases of cancer are diagnosed each year, making it the main cause of cancer-related mortality among Egyptian women [ 5 ]. The ratio of mortality/incidence rate of BC cases in Egypt was approximately double the ratio (41%) when compared with developed countries (23%) [ 6 ]. Many variables are associated with the risk of BC, including age, environmental, gynecological, and genetic factors [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, more than half of BC diagnoses and two-thirds of BC related deaths were reported in low- and middle-income countries in 2020 [ 2 ]. In Egypt, BC accounts for 38.8% of cancers in females, with the estimated number of BC cases nearly 22,700 in 2020 and is forecasted to rise exponentially over time [ 3 ]. Several factors contribute to BC heterogenicity including variations in genomic, epigenomic, transcriptomic, and proteomic characteristics of malignant cells.…”
Section: Introductionmentioning
confidence: 99%